A Review of the Mechanisms of Blood-Brain Barrier Permeability by Tissue-Type Plasminogen Activator Treatment for Cerebral Ischemia - Suzuki, Yasuhiro; Nagai, Nobuo; Umemura, Kazuo (Frontiers in Cellular Neuroscience, 2016)
Cerebrovascular homeostasis is maintained by the blood-brain barrier (BBB), which forms a mechanical and functional barrier between systemic circulation and the central nervous system. In patients with ischemic stroke, the recombinant tissue-type plasminogen activator (rt-PA) is used to accelerate recanalization of the occluded vessels. However, rt-PA is associated with a risk of increasing intracranial bleeding. This effect is thought to be caused by the increase in cerebrovascular permeability though various factors such as ischemic reperfusion injury and the activation of matrix metalloproteinases, but the detailed mechanisms are unknown. It was recently found that rt-PA treatment enhances BBB permeability not by disrupting the BBB, but by activating the vascular endothelial growth factor (VEGF) system. The VEGF regulates both the dissociation of endothelial-endothelial cell junctions and endothelial endocytosis, and causes a subsequent increase in vessel permeability through the VEGF receptor-2 activation in endothelial cells. Here, we review the possibility that rt-PA increases the penetration of toxic molecules derived from the bloodstream including rt-PA itself, without disrupting the BBB, and contributes to these detrimental processes in the cerebral parenchyma.